Demotivation in L2 Learning: A Quantitative Exploration of Engineering Students’ Perceptions - Gunawardena, S.J. (University of Jaffna, 2025)
L2 demotivation refers to internal and external forces that diminish motivation in second language learning. Accordingly, the limited success of many English language programmes is attributed to this. This study involved approximately 900 engineering undergraduates who completed a Likert-scale-based questionnaire. This questionnaire comprised eight subscales, namely, overall L2 demotivation, internal conflict in adopting an English speaking identity, external pressures preventing integration, negative learning environment, systemic barriers, social withdrawal, nationalism and ethnocentric undercurrents, and cultural or ideological resistance, each representing a facet of L2 demotivation. Formal statistical approaches on the Likert responses revealed an unexpected trend: the majority confirmed being motivated by disagreeing with demotivation-themed Likert items. The strongest to weakest demotives were: internal conflict in adopting an English speaking identity, negative learning environment, systemic barriers, social withdrawal, nationalism and ethnocentrism, externally imposed conflicts in integration, overall demotivation and cultural and ideological resistance. Controlling for gender differences, it was found that males were demotivated significantly more than the females by externally imposed conflicts in integration, negative learning environment, cultural and ideological resistance and systemic barriers, while both groups were affected similarly by the other quantities. Comparing Sinhala and Tamil speakers revealed that Sinhala speakers were demotivated significantly more by negative learning environment, social withdrawal and systemic barriers, and Tamil speakers were demotivated more by externally imposed conflicts in integration, while both groups were affected similarly by the other quantities. However, the most noteworthy demotives are revealed by Likert-scale items with relatively lower levels of disagreement as this cohort was largely motivated.
Keywords: Internal and external demotives; Engineering students; Quantitative research; Gender; L1